Needlestick prevention prior to Directive 2010/32/EU in a sample of Italian hospitals - Di Bari, Virginia; De Carli, Gabriella; Puro, Vincenzo; da HIV e altri patogeni a trasmissione ematica (SIROH), Gruppo collaborativo dello Studio Italiano sul Rischio Occupazionale (La Medicina del Lavoro, 2015)
Introduction: Needlesticks and cuts are the most common occupational injuries in healthcare workers (HCWs). Directive 2010/32/EU defines principles and preventive interventions. Objectives: To assess, in hospitals participating in the Italian Study on Occupational Risk of HIV (SIROH) project, which are very active in prevention, the degree of application of the measures provided for by the Directive, prior to its incorporation into Italian law. Methods: An open questionnaire covering the 9 focal points of the Directive, as a guide for a presentation at the SIROH meeting in 2013. Results: Of 100 SIROH hospitals, 97% and 96% respectively provide specific information and education initiatives (54% and 73% of which expressly for new employees). All centres reinforce the ban on recapping, and 30 monitor its application by inspecting sharps containers; all hospitals place containers on mobile trolleys and 78 provide operating procedures for their replacement; all introduced at least one needlestick-prevention device (NPD; 4 on average, range 1-11), most frequently intravenous catheters (91%) and winged needles (87%), but 39% only in selected units; 14 centres implemented initiatives to eliminate unnecessary needles. Regarding hepatitis B, all centres screen and vaccinate HCWs but only 78% monitor their response: 89% of HCWs were immunized. Post-exposure management protocols, although based on the same rationale, differ significantly causing considerable differences in costs. Conclusions: Most of the preventive interventions covered by the Directive were implemented in SIROH hospitals. It is necessary to invest in NPD availability and dissemination, elimination of unnecessary needles, and streamline post-exposure protocols. The situation in the remaining Italian facilities should be investigated.